The relationship between leg muscle strength, balance, and shooting accuracy in futsal players - Nur Hakim, Muhammad Reza; Solihin, Akhmad Olih; Syamsudar, Bangbang (Jurnal Ilmu Keolahragaan, 2025)
Background. Despite the physical demands of futsal, the combined effect of leg strength and balance on shooting accuracy remains underexplored, highlighting the need for integrated training based on observed performance gaps in youth players. Objectives. This study investigates the relationship between leg muscle strength and balance with shooting ability in futsal, emphasizing their combined impact on performance. Methods. A quantitative correlational research design was used, involving 20 high school futsal players selected through total sampling. Three measurement tests were conducted: a leg muscle strength test, a balance test, and a shooting ability test. Data analysis included Karl Pearson"™s product-moment correlation to examine individual relationships and multiple regression analysis to assess the combined effect of leg muscle strength and balance on shooting ability. Results. The findings indicate a significant relationship between leg muscle strength and shooting ability (Sig. = 0.046) and between balance and shooting ability (Sig. = 0.017), both with moderate correlation. Multiple regression analysis reveals that leg muscle strength and balance together have a strong relationship with shooting ability (R = 0.656), explaining 51% of its variance (R ² = 0.51, Sig. F Change = 0.043). These results suggest that enhancing leg muscle strength and balance can significantly improve shooting performance in futsal. Conclusion. This study highlights the importance of leg muscle strength and balance in shooting ability, with implications for sports training and physical education curricula. Integrating targeted strength and balance exercises can enhance shooting performance. Future research should explore additional factors such as coordination, agility, and psychological aspects to further optimize skill development in futsal and related sports.